Using design of experiments in the evaluation of the microstructural characterization parameters with the LePera reagent in a multiphase steel - De Faria Neto, Antonio Dos Reis [UNESP]; Fukugauchi, Cristina Sayuri; Dos Santos Pereira, Marcelo [UNESP] (IOP Publishing, 2021)
The performance of multiphase steels is closely related to their microconstituents. Thus, the characterization and effective control of the microstructure of these materials are crucial, and chemical attack processes are essential for this to occur. In this context, this study sought to employ the Taguchi method to evaluate the chemical etching process with the LePera reagent in order to investigate the influence of different process variables, in addition to the interactions between them, on the quality of the image obtained. The variables analyzed were: concentration of picral (CP) and sodium metabisulfite (CSM) solution, pre-attack (PA), drying mode (DM) and attack time (AT). in addition to the relative humidity and temperature of the environment. Therefore, a quality index (QI) was suggested for the images obtained, which, together with the analysis of variance, indicates the best route for microstructural characterization of TRIP800 steel (CP-4.0%; CSM-0.5% ; PA-No; DM-Natural; AT-25s; . Temperature ( C): 15I - -25 and Relative humidity (%): 55I - -90). In addition to indicating the variables that most influence the process. The influence of noise factors (temperature and relative humidity) was also proven.